Evaluation of Rice Bran as an Alternative Growth Medium for Rhizopus sp. - Dina Aribah; Mazidah Nabila Ridwan (Jurnal Laboratorium Khatulistiwa, 2026)
Rice bran is an abundant agroindustrial by-product with high nutritional content, yet its utilization in microbiology remains limited. Meanwhile, Rhizopus sp., widely used in laboratory research, requires a sustainable and cost-effective culture medium. This study aimed to evaluate the potential of rice bran as an alternative growth medium for Rhizopus sp. This study used rice bran media at concentrations of 5%, 10%, and 15% (w/v), with Sabouraud Dextrose Agar (SDA) as a control. Inoculation was performed using the single dot method. Mold growth was observed after 72 hours of incubation at ±30°C, both macroscopically and microscopically. Colony diameters were measured and analyzed using one-way ANOVA. The results showed that Rhizopus sp. grew well on all rice bran media, displaying complete vegetative and reproductive structures. Statistical analysis indicated no significant difference in colony diameter between rice bran media and SDA (p>0.05). These findings demonstrate that rice bran can serve as a cost-effective and sustainable alternative medium without compromising fungal growth quality.